Measurements in a 5:1 enlarged bio-centrifugal pump model - Ong, Kang Shiu. (2008)
This thesis consists of 2 sections. The Kyoto-NTN magnetically suspended centrifugal blood pump has shown its superiority compared to other artificial hearts, however, thombosis is found in the pump especially in the 0.2mm casing/impeller gap. It is thus required to find out the fluid mechanics related issues in the pump that are useful guidelines for the further computational and analytical pump optimum design and improvements. The present investigation aims to understand the flow field in the pump with three impellers that consist of 16 forward-swept, 16 straight and 8 backward-swept blades, with particular emphasis on the flow inside the impeller passages and the casing/impeller gap through 4 studies. As the casing/impeller gap is too small that no instruments is capable to measure the gap flow, a 5 times enlarged pump models have been designed and constructed, to facilitate the gap flow field investigations.